Does integration matter? an international cross-sectional study on the relationship between perceived public health and primary care integration and COVID-19 vaccination rates - Sumeet Sodhi; Rifka Chamali; Devarsetty Praveen; Manushi Sharma; Marcelo Garcia Dieguez; Robert Mash; Felicity Goodyear-Smith; David Ponka (PLoS ONE, 2025)
Background Immunisation against COVID-19 is crucial for controlling the pandemic, yet global challenges persist in vaccine coverage and equitable distribution. A well-integrated primary health care approach can enhance vaccination programmes. Aim To explore the relationship between perceived PC (primary care)-PH (public health) integration, as well as other vaccination program implementation factors, and national COVID-19 vaccination coverage. Design and setting A convenience sample of self-identified primary care professionals completed an online survey on COVID-19 vaccination programme implementation and their perceptions of PC-PH integration. Methods Countries with ≥5 responses were included in the data analysis. COVID-19 vaccination implementation approach and perceived PC-PH integration against COVID-19 vaccination coverage was investigated using bivariate and subgroup analyses, Spearman correlation, and linear regression. Results A total of 394 responses from 32 countries were analysed. Participants included primary care providers, academics, and researchers. The median national COVID-19 vaccination coverage was 28.41% at time of study. Perceived barriers included patient hesitancy and vaccine supply shortages, while facilitators included vaccine product choices, equity, and community engagement. The study revealed a positive relationship between perceptions of PC-PH integration and national vaccination coverage in upper-middle and lower-middle income countries. Conclusion Perceived PC-PH integration increased with decreasing economic quartiles and this perception was linked to actual national vaccination coverage. Integration may be especially important for countries with lesser vaccine supply. High-income countries may benefit from increased collaboration between PC and PH to enhance vaccination efficiency. The findings contribute to understanding the role of PC-PH integration in vaccination programmes in different settings.